Malaysia a pictorial history, 1400-2004 Wendy Khadijah Moore - Moore, Wendy (Archipelago press, 2004)
Documents the history of Malaysia from the beginning of the Melakan Sultanate approximately 600 years ago to the emergence of Malaysia as a modern nation during the last two centuries.